Analisis Perancangan Jaringan Fiber to The Home Area Universitas Nasional Blok IV dengan Optisystem - Efan Nuari; Iskandar Fitri; Nurhayati Nurhayati (STMIK Budi Darma, 2020)
Researchers will be designing the access network Fiber To The Home (FTTH) on the technology of Gigabit Passive Optical Network (GPON). The location that became the case study was the National University of Block IV, where the network speed at the site was slightly reduced speed. The purpose is to get the design of an access service network that is expected to be implemented for triple play services. Starting with data collection of data. The Fiber To The Home (FTTH) network design determining device specification, layout and number of devices used and simulated using Optisystem application. Then in the analysis based on predefined parameters in the form of BER (Bit Error Rate), Link Power Budget, and Rise Time Budget that meet the optical network with the standard of PT. Telkom. The results of the BER value has fulfilled the minimum BER value specified for fiber optic is 10-9 and for parameter Q – Factor obtained value 9,32288 so that has been meets the standard because it shows values above 6